ADAT AND SHARIA IN THE FRAMEWORK OF INHERITANCE LAW AMONG THE PEOPLES OF DAGESTAN IN THE 17TH-19TH CENTURIES - Abdulmazidov, Ramazan Sultanovic; Tupcokova, Larisa Kazbekovna (History, Archeology and Ethnography of the Caucasus, 2019)
The article introduces a study of adat and sharia interaction within the hereditary law of the peoples of Dagestan. Researchers of legal culture of the peoples of the North Caucasus often made mistakes considering this sphere of legal relations, in connection with which attention was drawn to the most characteristic of them. Moreover, the article reveals the order of inheritance under Muslim law, analyzes the norms of inheritance law contained in the Dagestan collections of adats. The issues that caused the most heated debate, in particular, on depriving women of the share of real property and the application of “nazr” (vow) in the division of inheritance, have been examined. An analysis of the adat norms recorded in the Dagestan legal monuments that regulated inheritance relations indicates a long-standing confrontation between the adat and the sharia in this area of law. Despite the assertion of the priority of the establishment of sharia in Dagestan, adat also retained a certain value with the strengthening of the position of Islam. Socio-economic realities determined the preservation of the norms of the adat laws, which led to a certain symbiosis of the two legal systems in the inheritance law of the peoples of Dagestan.
Keywords: Dagestan; legal culture; Muslim law; adat; inheritance law.